The Effect of Box Height during Drop Landing on Risk Factors of Anterior Cruciate Ligament Injury in Female Players - Sunghe Ha; Sang-Kyoon Park (Asian Society of Kinesiology, 2018)
OBJECTIVES This study investigated biomechanical risk factors of the anterior cruciate ligament (ACL) injury as well as muscle activation patterns in the lower extremity according to the increase of box height in female soccer players. METHODS Twenty-three professional female soccer players participated in this study. Thigh muscle activation patterns, knee joint kinematics, and kinetics were analyzed during drop landing from 30cm and 50cm. Statistical analysis was carried out with a paired t-test to compare the risk factors of anterior cruciate ligament damage in the population with increasing box height. RESULTS The activation of anterior part of thigh was significantly increased in drop landing from 50cm compared with 30cm, but no significant posterior part. As the box height increased, protective mechanisms of ACL injury were observed increasing ACL injury risk in drop landing. CONCLUSIONS The hamstring training to maintain stability of the knee joint and limit anterior translation of the tibia may diminish risk of the anterior cruciate ligament injury.